2023
DOI: 10.1186/s12876-023-02756-w
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and sarcopenia are common and insufficiently diagnosed among chronic pancreatitis patients

Abstract: Purpose Chronic pancreatitis (CP) leads to diabetes and pancreatic exocrine insufficiency (PEI). PEI may lead to maldigestion and malnutrition, which may cause fat-soluble vitamin deficiency, sarcopenia and abnormal bone density. We aim to study the prevalence of osteoporosis, sarcopenia and vitamin deficiency among CP patients. Methods Long-term (4–5 years) follow-up was implemented on CP patients. We recorded CP duration, BMI, smoking, alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…9 Many patients with gastrointestinal diseases, such as inflammatory bowel disease, severe liver disease, and various forms of pancreatitis, frequently undergo abdominal CT or MRI scans that enable psoas muscle mass at the L3 or L4 vertebra level to be calculated. [10][11][12][13] Moreover, it is easier to measure PMA than to measure the area of skeletal muscles. Because MRI requires much more time and is costlier than CT, all patients with AP in the present study underwent CT scanning, with only a few undergoing MRI after CT.…”
Section: Discussionmentioning
confidence: 99%
“…9 Many patients with gastrointestinal diseases, such as inflammatory bowel disease, severe liver disease, and various forms of pancreatitis, frequently undergo abdominal CT or MRI scans that enable psoas muscle mass at the L3 or L4 vertebra level to be calculated. [10][11][12][13] Moreover, it is easier to measure PMA than to measure the area of skeletal muscles. Because MRI requires much more time and is costlier than CT, all patients with AP in the present study underwent CT scanning, with only a few undergoing MRI after CT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increase in pro-inflammatory cytokines in blood serum (interleukin 1 beta (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor alpha (TNFα)), as well as inflammatory indicators (C-reactive protein (CRP), lactate dehydrogenase (LDH), gamma-glutamyltransferase (GGTP), superoxide dismutase (SOD), and reduced glutathione (GSH)) were observed in the pigs, confirming systemic inflammation [7]. There is a clear association between chronic systemic inflammation and osteoporosis (OP), a systemic bone metabolic disorder characterized by deteriorating bone microarchitecture and increased bone vulnerability [8,9] which contributes to accelerated bone loss and an increased risk of fractures in affected individuals [10,11]. Additionally, osteoporosis may coexist with conditions such as osteoarthritis [12,13], a complex disease that leads to joint pain, reduced joint mobility, and impaired joint function [14,15].…”
Section: Introductionmentioning
confidence: 92%
“…osteopenia, osteoporosis) in patients with CP ranged from 36.5% to 57.0%. 22 27 The observational study ‘ Prospective Evaluation of Chronic Pancreatitis for Epidemiologic and Translational Studies (PROCEED Study) ’ was completed in 2022. A cross-sectional analysis from the PROCEED study involving 282 patients with CP showed that the prevalence of osteopathy on dual-energy X-ray absorptiometry scan was 56.0%, and higher prevalences of traumatic and spontaneous fracture were observed in the cohort of CP patients with osteopathy.…”
Section: Nutritional Supportmentioning
confidence: 99%